Scientific Modelling of Socially Acute Questions to Promote Citizenship Action with Preservice Early Childhood Teachers. - Cebrián-Robles, Daniel; España-Ramos, Enrique; Cruz-Lorite, Isabel María; España-Naveira, Paloma; González-García, Francisco José; Cabello-Garrido, Aurelio; Cabello-Garrido (My University, 2023)
This paper studies the impact of modelling practice through multiple models. It was carried out in a training programme of collective activism based on scientific practices with preservice early childhood teachers at Málaga University (Spain) during 2021/22. The programme has 4 phases: 1) inquiry, 2) action planning, 3) action and 4) evaluation and reflection. Eleven activist projects were carried out on controversial local issues, selected by 11 teams of 4 or 5 students. The students' answers to two open-ended questions on the assessment of the modelling activity for the development of their activist project are analysed using a system of categories created inductively. According to most students, modelling has had a positive effect on the realisation of their activist projects, not only helping them acquire knowledge but also enabling them to become aware of their views and develop competences to carry out the project. The most difficult part was to identify and/or relate the multiple problem factors in the model and to delimit the project to be represented. However, the quality of the work improved compared to previous years when modelling was not considered.
Keywords: Problemas sociales - Estudio y enseñanza; Didáctica; Modelling; Collective Activism; Science Education; Socially acute questions; Preservice teachers